Impact of Vortioxetine with antiepileptic drugs combined administration on non- convulsive behaviour in kindled rats - Ostapenko, I. (Journal of Education, Health and Sport, 2023)
Epilepsy is a prolonged, progressively advancing nervous and psychiatric disorder of various etiologies, characterized by paroxysmal and relatively persistent psychological disturbances. A significant burden of comorbid pathology is attributed to psychiatric disorders. Depressive disorders are among the most common behavioral comorbidities in patients with epilepsy, often remaining undiagnosed and untreated. The approach to treating depression in epilepsy patients is currently underdeveloped. To fully understand the prospects of the experimental framework for minimizing and/or eliminating depressive behavioral manifestations during the interictal period under conditions of chronic epileptogenesis, we conducted a series of studies to determine the effectiveness of comprehensive correction of non-seizure behavior in kindling animals. The aim of this study is to delineate alterations in the expression of non-seizure behavior in rats due to the combined administration of Vortioxetine with antiepileptic drugs in the dynamic context of chronic kindling-induced seizure activity. It has been established that in rats during the development of Picrotoxin-induced chronic epileptic syndrome, disruptions in late-tonic, emotional, and swimming types of behavior are observed, which are manifestations of non-seizure behavior. It has been proven that the combined administration of Valproic acid and Vortioxetine results in successful correction of the tested forms of behavior. Less effectiveness is observed with vortioxetine alone, and the least effectiveness is noted in a smaller number of investigated behavior types after valproic acid administration. The data demonstrate balancing systemic-antisynergistic relationships, the imbalance of which during the development of picrotoxin-induced chronic epileptic syndrome allows the development of non-seizure behavior forms during interictal periods. The obtained data and their analysis provide experimental groundwork for the appropriateness of clinically testing the combined administration of Vortioxetine with Valproic acid as part of complex therapy in epilepsy patients with the presence of a depressive behavioral component.